NMR Spectroscopy and Metal Ions in Life Sciences. Issue 44 (2nd October 2018) - Ravera, Enrico; Takis, Panteleimon G.; Fragai, Marco; Parigi, Giacomo; Luchinat, Claudio
Abstract : Metal ions play important structural and functional roles in many biological systems. The NMR spectroscopic characterization of biomolecules not only had to deal with the need of taking them into account, but also successfully exploited the characteristics of the paramagnetic metals to obtain structural information. The latter proved so important that diamagnetic proteins are in several cases made paramagnetic through substitution of a diamagnetic metal ion with a paramagnetic one or attachment of a paramagnetic tag. NMR studies of metal ions are also important for biomedical applications. Examples are provided here in the field of drug discovery and the development of contrast agents for MRI. More recently, paramagnetic metals proved useful also for improving the NMR sensitivity by dynamic nuclear polarization. Finally, NMR metabolomics studies are emerging for the identification and quantification of metal ions present in biological fluids. Abstract : NMR spectroscopy is a powerful tool for the exploitation of metal ions and their properties to improve our understanding of biology, to contribute to medical diagnosis, and to provide novel analytical tools for inorganic ions in complex biological matrices.